Existence Of Corporate Governance In Indonesian State-Owned Enterprises - Saring Suhendro (Universitas Muhammadiyah Prof. DR HAMKA., 2022)
The sample consisted of 72 non-financial Indonesian state-owned businesses. The overall corporate governance score in 2020 is based on the annual report. The main goals of this study are to comment on Indonesia's state-owned firm self-assessment system, evaluate the relative importance of various klaster industries, and give extensive information on each corporate governance implementation. The energy, oil and gas klaster, mineral and coal klaster, infrastructure klasters, and logistics klasters are shown to have the strongest predictive value of business results in this study. With a score of above 90, this is a very excellent predictor. The score evaluation results for health, logistics, telecommunications, tourism, and support klasters reveal a score attainment of 85-90 with a very excellent predicate. Manufacturing klaster, tourism klaster, and support klaster all have a positive outlook. Corporate governance has a good and large impact on Indonesian state-owned firms, according to empirical research. Only a sample of Indonesian state-owned firms was used in this study.